Analysis of the Implementation of the Rights of Patients with Mental Disorders to Access Health Services in HospitalsProf. Dr. Muhammad Ildrem North Sumatra - Farhan; Muhammad Arif Sahlepi; Irsyam Risdawati (Equivalent : Journal of Economic, Accounting and Management, 2026)
The rights of patients with mental disorders are an integral part of efforts to provide fair and equitable health services. In this context, hospitals as health institutions have a responsibility to ensure that patients with mental disorders get their rights, including access to quality health services. This research focuses on the implementation of the rights of patients with mental disorders in obtaining access to health services at Prof. Dr. Muhammad Ildrem Hospital, North Sumatra. The main focus of this study is to evaluate the extent to which the rights of patients with mental disorders are guaranteed and fulfilled in the hospital service system. This study uses a qualitative approach with a descriptive type of research. Data was collected through in-depth interviews with relevant parties, such as medical personnel, patients with mental disorders, and hospital managers. In addition, direct observation of health service practices in hospitals is also carried out to get a more complete picture of the implementation of patient rights. This study aims to analyze the extent of the implementation of the rights of patients with mental disorders at Prof. Dr. Muhammad Ildrem Hospital. and to find out the factors that affect patients' access to health services, as well as to identify obstacles and challenges faced in the implementation of patients' rights. The results of the study show that although there are policies that support the protection of the rights of patients with mental disorders, their implementation in the field still faces various challenges. Some of the factors that affect access to health services for patients with mental disorders include social stigma against mental disorders, limited facilities and trained human resources, and lack of adequate understanding from some medical workers regarding the rights of patients with mental disorders. Conclusion of this study The implementation of the rights of patients with mental disorders at Prof. Dr. Muhammad Ildrem Hospital still needs to be improved, especially in terms of fulfilling access to health services in accordance with their rights. Social stigma and limited resources are the main obstacles that need to be overcome.